Optimalisasi Sekretariat Komite Mutu Dalam Meningkatkan Kinerja Komite Mutu Di Rumah Sakit - Aisyiah, Intan Kamala; Rani, Ica Efendi Sandra; Kholisa, Tazkya; Syahra, Syahra; Piscesha, Lathifah Aini; Rahmawati, Lusi; Yurmanelis, Yurmanelis; Himendra, Ghazi Pratama (Yayasan Jompa Research and Development, 2025)
Improving the quality of healthcare services in hospitals is significantly influenced by the effectiveness of the Quality Committee, including the support provided by its secretariat. This study aims to identify the root causes of problems in the management of the Quality Committee Secretariat and to develop optimization strategies. The research employed a field study method through observation, interviews, and document review. The findings revealed several challenges, such as the absence of full-time staff in the secretariat, lack of a duty schedule, and inadequate coordination and documentation. Using the fishbone approach and the Plan-Do-Study-Act (PDSA) cycle, solutions were implemented, including the establishment of duty schedules, attendance tracking, and the reactivation of the documentation system. Initial evaluation indicated improved attendance and greater involvement of the secretariat staff in quality activities. This study concludes that optimizing the Quality Committee Secretariat plays a crucial role in enhancing the effectiveness of quality improvement and patient safety programs. Hospitals are encouraged to conduct regular monitoring to support the sustained performance of the Quality Committee.